Cardioversion of acute atrial fibrillation in the emergency department: a prospective randomised trial. Issue 3 (21st March 2011) - Bellone, Andrea; Etteri, Massimiliano; Vettorello, Marco; Bonetti, Chiara; Clerici, Dante; Gini, Giancarlo; Maino, Carlo; Mariani, Massimo; Natalizi, Anna; Nessi, Italo; Rampoldi, Alessandro; Colombo, Livio
Abstract : Background: Strategies to restore sinus rhythm in patients with atrial fibrillation (AF) lasting less than 48 h with haemodynamic stability remain controversial. The aim of this study was to test the hypothesis that electrical cardioversion (EC) would be more effective and safer in converting acute AF to sinus rhythm, compared with intravenous propafenone treatment. Methods: In the emergency department (ED) of Valduce Hospital, a single-centre randomised trial was conducted to compare EC with pharmacological cardioversion (PC) to restore the sinus rhythm in selected patients with acute AF. A total of 247 patients was enrolled (121 in the EC group and 126 in the PC group). Results: EC was more successful than PC in restoring sinus rhythm. Successful cardioversion was achieved in 108 out of 121 patients in the EC group (89.3%) and 93 out of 126 patients in the PC group (73.8%) (HR in the EC group, 0.34; 95% CI 0.17 to 0.68; p=0.02). The time patients spent in the ED undergoing treatment was significantly lower in the EC group compared with the PC group (median (range), 180 (120–900) vs 420 (120–1400) min; p<0.001). Conclusions: EC was more effective in patients with acute AF and resulted in a shorter length of stay in the ED than PC. Adverse events were small in number and transient in both groups of patients. Clinical trials registration number: NCT00933634.